Compliance of Junior Secondary School Building Layouts with the National Education Standards: A Case Study of Depok City - Anedya Wardhani; Yulita Hanifah (Jurnal Lingkungan Binaan Indonesia, 2026)
School buildings play a vital role in education by serving as physical spaces for learning and environments that affect comfort, safety, and the effectiveness of the learning process. At the junior secondary school (SMP) level, providing adequate facilities and infrastructure is crucial because students are in a transitional phase of cognitive and social development that requires a safe and functional learning environment. In urban areas, meeting educational infrastructure standards often faces challenges such as limited land availability, high population density, and increasing student numbers, all of which influence the layout of school buildings. This study aims to evaluate whether the building layout and facilities of junior secondary schools in Depok City conform to the infrastructure standards set by the National Education Standards. The research uses a descriptive quantitative approach involving 34 schools, considering school capacity, land area, building size, and classroom conditions. The results indicate that land capacity is closer to the standard compared to classroom capacity. However, the imbalance between the number of classrooms and students still causes classroom overcrowding. Overall, most schools fall into the moderate compliance category (58%), with only a small percentage fully meeting the standards, highlighting the need for improvements in educational infrastructure.